The Gateway to Computer Science Excellence
0 votes
113 views

 

in Digital Logic by | 113 views
+1
I'm getting :-
3*6 + 6*8 + 3 + 87 + x = 2*9*9 + 3*9 + 5 ===> x = 33

Now here i'm confused a bit should the answer be 33 or 113 as (33)base10 = (113)base5
Because we're asked value of x ?
According to me it should be 113 am i right ?
0

3*6+5+6*8+3+8*10+7=36+5+48+3+80+7=41+51+87= 179

(235)9=2*81+3*9+5=162+27+5=  194

194-179=(15)10=(30)5

Ans=30

+1
yes 113 is the correct answer

what's the answer given ??
0
It is 113 well i got it now thnx :)
+3

you are evaluate that expression in decimal, let (x)5 = (y)10 . ------ For avoiding confusion

3*6 +5+ 6*8 + 3 + 87 + x = 2*9*9 + 3*9 + 5

should be wrote as

3*6 +5+ 6*8 + 3 + 87 + y = 2*9*9 + 3*9 + 5 ===> y=33 then what is x?

(x)5 = (33)10

0
@ Shaik, ohkk now i got that properly

Please log in or register to answer this question.

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
52,315 questions
60,427 answers
201,757 comments
95,235 users